POLA KOMUNIKASI SEKAA ARJA MUANI DALAM MEMBANGUN CITRA PENARI CROSS GENDER (Studi pada Sekaa Arja Maha Tjandra di Kabupaten Gianyar) - Lestari, Putu Gita; Suryawati, I Gusti Agung Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2024)
Sekaa Arja Maha Tjandra is sekaa arja muani which is a performing arts group that has only male members. The female and male characters in arja muani performed by male, known as cross gender dancers. Dancer phenomenon cross gender is one that is being discussed related to sekaa arja muani in the current era. Group communication is the most important point in determining the direction of group development. As part of a group, all individuals in it should have full responsibility for their own group. This study uses the Laswell Communication Model to find out and explain the communication patterns used by Sekaa Arja Maha Tjandra in building the image of cross gender dancers. This type of research is qualitative using data collection techniques in the form of interviews, observation, and documentation. The results showed that there were two communication patterns used by Sekaa Arja Maha Tjandra, namely the wheel communication pattern and the star communication pattern or all channels. There is a uniqueness in the interaction among members of Sekaa Arja Maha Tjandra that distinguishes it from the other sekaa arja muani.